1997
DOI: 10.1093/tropej/43.5.282
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium infection in children in urban Bangladesh

Abstract: We reviewed data during 1991-94 from a systematic 4 per cent subsample of all patients who presented with diarrhoea to our facility, in which there were 1949 cases of acute diarrhoea in children between the ages of birth to 59 months. Cryptosporidia oocysts were detected in the stools of 68 (3.5 per cent) of these children. A case-control study was designed using surveillance data which included the 68 children with stool positive for Cryptosporidium as cases. Two hundred and four children who did not have Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…However, the direction of causation could not be identified, and so we cannot determine whether stunting is caused by the infection or whether children are predisposed to infection when stunted. Previous studies from India and Peru have also identified a similar relationship between Cryptosporidium infection and stunting [8,30].…”
Section: Discussionsupporting
confidence: 59%
“…However, the direction of causation could not be identified, and so we cannot determine whether stunting is caused by the infection or whether children are predisposed to infection when stunted. Previous studies from India and Peru have also identified a similar relationship between Cryptosporidium infection and stunting [8,30].…”
Section: Discussionsupporting
confidence: 59%
“…In developing countries, Cryptosporidium infections occur mostly in children younger than 5 years, with peak occurrence of infections and diarrhea in children younger than 2 years (21,22,154). Children can have multiple episodes of cryptosporidiosis, indicating that acquired immunity to Cryptosporidium infection is short-lived or incomplete (154,248).…”
Section: Introductionmentioning
confidence: 99%
“…Although cryptosporidiosis is widely prevalent in Bangladesh (2,4,16,19,20,23,24), there have been no studies on the genetic diversity of Cryptosporidium spp. in this country.…”
mentioning
confidence: 99%